2012
DOI: 10.3727/096368912x640493
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Myogenic Potential of Mesenchymal Stromal Cells Isolated from Umbilical Cord

Abstract: Nonhematopoietic cord blood cells and mesenchymal cells of umbilical cord Wharton's jelly have been shown to be able to differentiate into various cell types. Thus, as they are readily available and do not raise any ethical issues, these cells are considered to be a potential source of material that can be used in regenerative medicine. In our previous study, we tested the potential of whole mononucleated fraction of human umbilical cord blood cells and showed that they are able to participate in the regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 92 publications
(80 reference statements)
2
41
0
Order By: Relevance
“…Focusing on the skeletal muscle repair and regeneration, and apart from muscle-derived cells, the most popular source of MSCs is still the bone marrow. However, MSC populations are present in virtually all body tissues, and alternative sources have been proposed, such as adipose tissue, synovial membrane [2,73,74], dental pulp [4,69,75], and even umbilical cord tissue [76,77]. Cells from these sources display comparable phenotypical features regarding their "stemness" potential (they are plastic adherent, positive for markers of the mesenchymal and negative for the hematopoietic lineage markers).…”
Section: Mscs' Sources For Skeletal Muscle Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on the skeletal muscle repair and regeneration, and apart from muscle-derived cells, the most popular source of MSCs is still the bone marrow. However, MSC populations are present in virtually all body tissues, and alternative sources have been proposed, such as adipose tissue, synovial membrane [2,73,74], dental pulp [4,69,75], and even umbilical cord tissue [76,77]. Cells from these sources display comparable phenotypical features regarding their "stemness" potential (they are plastic adherent, positive for markers of the mesenchymal and negative for the hematopoietic lineage markers).…”
Section: Mscs' Sources For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…As an example, the myogenic potential of MSCs from the synovial membrane (SM-MSCs) seems more limited than for chondrogenesis, osteogenesis, or adipogenesis since only limited number of individually expanded clones presented myotube formation capacity, suggesting subpopulations with specific tendencies for lineage commitment [73]. MSCs isolated from the umbilical cord stromal tissue display limited intrinsic tendency toward myogenic lineage differentiation, expressing diminished levels of pluripotency and specific myogenic markers involved in such process (such as Oct-4, Nanog, Pax-7, MyoD and myogenin, and M-cadherin), and they do not seem to spontaneously differentiate toward this lineage [76]. Conversely, when cocultured with differentiating myoblasts, differentiation can be observed [76].…”
Section: Evidence Of the In Vitro Myogenic Differentiation Potential mentioning
confidence: 99%
See 1 more Smart Citation
“…In a different mouse model of muscle injury, only a limited fraction of hUC-MSCs were in fact found to express markers of pluripotent and myogenic cells, such as octamer-binding transcription factor 4 (OCT-4) and Nanog and only a minority of cells actually participated in new muscle fiber and myotube formation (27). Therefore, these results indicated that hUC-MSCs possessed only limited potential for promoting granulation.…”
Section: Discussionmentioning
confidence: 76%
“…It has been suggested that hUC-MSCs function similar to bone marrow-derived MSCs, the biological activities of which include paracrine signaling by trophic factors, the secretion of growth factors and cytokines, and the regulation of the proliferation and migration of endogenous cells (such as satellite cells and other muscle-related cells) (27,28). The source of the beneficial trophic and/or growth factors may be either endogenous cell types or the transplanted MSCs or both.…”
Section: Discussionmentioning
confidence: 99%